Human placental villi contain stromal macrovesicles associated with networks of stellate cells. Issue 1 (11th September 2019) - Palaiologou, E.; Etter, O.; Goggin, P.; Chatelet, D. S.; Johnston, D. A.; Lofthouse, E. M.; Doherty, R.; Pearson‐Farr, J.; Sengers, B. G.; Torrens, C.; Cleal, J. K.; Page, A. M.; et al.
Abstract: Placental function is essential for fetal development and establishing the foundations for lifelong health. The placental villous stroma is a connective tissue layer that supports the fetal capillaries and villous trophoblast. All the nutrients that cross the placenta must also cross the stroma, and yet little is known about this region. This study uses high‐resolution three‐dimensional imaging to explore the structural complexity of this region within the placental villi. Serial block‐face scanning electron microscopy and confocal microscopy were used to image the placental villous stroma in three‐dimensions. Transmission electron microscopy (TEM) was used to generate high resolution two‐dimensional images. Stereological approaches were used to quantify volumes of stromal constituents. Three‐dimensional imaging identified stromal extracellular vesicles, which constituted 3.9% of the villous stromal volume. These stromal extracellular vesicles were ovoid in shape, had a median length of 2750 nm (range 350–7730 nm) and TEM imaging confirmed that they were bounded by a lipid bilayer. Fifty‐nine per cent of extracellular vesicles were in contact with a fibroblast‐like stellate cell and these vesicles were significantly larger than those where no contact was observed. These stellate cells formed local networks with adherent junctions observed at contact points. This study demonstrates that the villous stroma contains extracellular macrovesicles which are considerably larger than any previously described in tissue or plasma. The size and abundance of these macrovesicles in the villous stroma highlight the diversity of extracellular vesicle biology and their roles within connective tissues. Abstract : Extracellular vesicles are membrane‐bound structures released from cells into the plasma or stroma. Extracellular vesicles are thought to contain chemical messengers and have a signalling function. The two main classes of extracellular vesicle are exosomes and microvesicles, although because of their overlapping size distributions these cannot always be readily distinguished. Stromal extracellular vesicles are typically <300 nm in diameter but the placental villous stroma contains much larger ovoid stromal macrovesicles with a median length of 2750 nm. Villous stromal vesicles made up 3.9% of villous stromal volume.